Strategi Indonesia Dalam Kepemimpinan ASEAN 2011 (Analisis Peranan Indonesia Sebagai Penengah Konflik Thailand-Kamboja Tahun 2008-2011) - Putra, Triawan; Utomo, M.A, Drs. Tri Cahyo; Windiani, M.S, Dr. Reni (Journal of Politic and Government Studies, 2013)
This research describes the role of Indonesia as mediator Thailand-Cambodia border conflict while Indonesia as ASEAN Chair 2011. Conflict between Thailand and Cambodia a few years ago made ​​the other members of ASEAN advise both parties to resolve their conflict, because being bother cooperation among ASEAN countries. Therefore, in order not expand, this conflict should be resolve. A failure of bilateral coopration in order to conflict resolution making interference by ASEAN and the UN. A decision had been delegated by United Nations to ASEAN to resolve this conflict. The Government of Indonesia as mediator had helped both meet and negotiate in Indonesia. Indonesia has offered a solution, but it has not been done because it is still awaiting approval from the cabinet and parliament Thailand. After mediation by Indonesia, relations between Thailand-Cambodia have already better, and also boundary conditions have been conducive. Although it has not achieve a peace agreement.